Novel multicomponent composite with TiO2/Y2O3 as cathode material and interlayer for Li-SPAN batteries cycled at high C-rates - Paez Jerez, Ana Laura (2023)
A novel multicomponent composite within the broad sulfurized polyacrylonitrile family of composites (SPAN) was synthesized. This innovative composite, termed as SPAN/Ti-Y, was composed of S, PAN, TiO2 and Y2O3. Cathodes were made using a two-step coating technique, resulting in two regions with synergistic functions. The first region is built on the multicomponent composite while the second zone is prepared with the mixture of metal oxides only. The present work describes a different Li-SPAN cell, standing out for its third and fourth components of TiO2/Y2O3 which accomplish two vital functions as both modifying the SPAN cathode materialand as an interlayer between cathode and separator. An extensive morphological, structural and electrochemical characterization of the composite was performed. The content of S and TiO2/Y2O3 was 40.6% (29.9% sulfur according to ICP-OES and elemental analysis, and 10.7% TiO2/Y2O3, according to TGA). Through XPS analysis of the as-synthesized composite and cells that underwent different number of cycles, a better understanding of the molecular structure can be suggested. When proved as cathode material, the cell reached capacity values of 1528 mAh g 1 for the 5th cycle and 907 mAh g 1 after 850 cycles (results express per mass of S + TiO2/Y2O3), with a capacity fading per cycle of 0.07%, at 3 C in simple carbonate-based electrolytes. These values are superior that a SPAN cathode material with commercial TiO2. Our results lead us to think that TiO2 mixed with Y2O3 could act not only as a valuable second active component but also as an electrocatalyst, and the electrochemical reactions of sulfur could be combined with the insertion/extraction of lithium within the structure of TiO2/Y2O3.